Incorporating LsrK AI‐2 quorum quenching capability in a functionalized biopolymer capsule. Issue 2 (16th October 2017) - Rhoads, Melissa K.; Hauk, Pricila; Terrell, Jessica; Tsao, Chen‐Yu; Oh, Hyuntaek; Raghavan, Srinivasa R.; Mansy, Sheref S.; Payne, Gregory F.; Bentley, William E.
Abstract: Antibacterial resistance is an issue of increasing severity as current antibiotics are losing their effectiveness and fewer antibiotics are being developed. New methods for combating bacterial virulence are required. Modulating molecular communication among bacteria can alter phenotype, including attachment to epithelia, biofilm formation, and even toxin production. Intercepting and modulating communication networks provide a means to attenuate virulence without directly interacting with the bacteria of interest. In this work, we target communication mediated by the quorum sensing (QS) bacterial autoinducer‐2, AI‐2. We have assembled a capsule of biological polymers alginate and chitosan, attached an AI‐2 processing kinase, LsrK, and provided substrate, ATP, for enzymatic alteration of AI‐2 in culture fluids. Correspondingly, AI‐2 mediated QS activity is diminished. All components of this system are "biofabricated"—they are biologically derived and their assembly is accomplished using biological means. Initially, component quantities and kinetics were tested as assembled in microtiter plates. Subsequently, the identical components and assembly means were used to create the "artificial cell" capsules. The functionalized capsules, when introduced into populations of bacteria, alter the dynamics of the AI‐2 bacterial communication, attenuating QS activated phenotypes. We envision the assembly of these and other capsules or similar materials, as means to alter QS activity in a biologically compatible manner and in many environments, including in humans. Abstract : "Quorum quenching" capsules silence bacterial "crosstalk" by modifying bacterial autoinducer, AI‐2. Capsules are assembled from natural polysaccharides, alginate and chitosan, and tethered to AI‐2 kinase, LsrK. They also contain LsrK substrate, ATP, which diffuses from the capsule and reacts with LsrK. The phosphorylated form of Ai‐2 does not activate quorum sensing phenotypes.